Magnetic Fields in the Solar Convection Zone - Fan Yuhong (Living Reviews in Solar Physics, 2004)
Recent studies of the dynamic evolution of magnetic flux tubes in the solar convection zone are reviewed with focus on emerging flux tubes responsible for the formation of solar active regions. The current prevailing picture is that active regions on the solar surface originate from strong toroidal magnetic fields generated by the solar dynamo mechanism at the thin tachocline layer at the base of the solar convection zone. Thus the magnetic fields need to traverse the entire convection zone before they reach the photosphere to form the observed solar active regions. This review discusses results with regard to the following major topics: 1. the equilibrium properties of the toroidal magnetic fields stored in the stable overshoot region at the base of the convection zone, 2. the buoyancy instability associated with the toroidal magnetic fields and the formation of buoyant magnetic flux tubes, 3. the rise of emerging flux loops through the solar convective envelope as modeled by the thin flux tube calculations which infer that the field strength of the toroidal magnetic fields at the base of the solar convection zone is significantly higher than the value in equipartition with convection, 4. the minimum twist needed for maintaining cohesion of the rising flux tubes, 5. the rise of highly twisted kink unstable flux tubes as a possible origin of d -sunspots, 6. the evolution of buoyant magnetic flux tubes in 3D stratified convection, 7. turbulent pumping of magnetic flux by penetrative compressible convection, 8. an alternative mechanism for intensifying toroidal magnetic fields to significantly super-equipartition field strengths by conversion of the potential energy associated with the superadiabatic stratification of the solar convection zone, and finally 9. a brief overview of our current understanding of flux emergence at the surface and post-emergence evolution of the subsurface magnetic fields.